Penerapan Hukum Waris Islam Pasca Berlakunya Kompilasi Hukum Islam di Indonesia - Hariati, Sri (Universitas Mataram, 2024)
The Compilation of Islamic Law (Kompilasi Hukum Islam/KHI), enacted through Presidential Instruction No. 1 of 1991, serves as a crucial legal foundation for inheritance issues among Muslims in Indonesia. KHI was developed to provide legal certainty and justice in the distribution of inheritance and to unify previously pluralistic inheritance regulations. This article aims to analyze the implementation of inheritance law based on KHI and highlight the challenges faced in its application, particularly from the perspective of justice and legal certainty. This study employs a normative juridical approach and comparative analysis to compare KHI with customary law across various regions. The findings indicate that while KHI has succeeded as a guideline in inheritance law, there are significant challenges in harmonizing it with customary laws and in raising public legal awareness. Religious courts also face dilemmas in enforcing KHI amid differing local traditions. Therefore, further efforts are needed to enhance public understanding and harmonize KHI with customary laws.